Comparing the Effectiveness of Cognitive-Behavioral Couple Therapy and Emotionally Focused Couple Therapy on Romantic Relationship Perfectionism in Couples with Conflict - Zamani Khormandichali, Davoud; Noruzi, Asghar; Akbarnataj Bisheh, Kolsoum (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to compare the effectiveness of cognitive-behavioral couple therapy and emotionally focused couple therapy on romantic relationship perfectionism among couples experiencing marital conflict.Methods and Materials: The present study employed a quasi-experimental pretest–posttest design with a control group and a three-month follow-up period. The statistical population consisted of all couples referring to counseling centers in Districts 21 and 22 of Tehran in 2025. Using purposive sampling and G*Power software, 45 couples meeting the inclusion criteria were selected and randomly assigned into two experimental groups and one control group, with 15 couples in each group. Data collection instruments included the Romantic Relationship Perfectionism Scale developed by Matte and Lafontaine (2012) and the Marital Conflict Questionnaire developed by Sanaei and Barati (1999). The first experimental group received cognitive-behavioral couple therapy based on Dattilio’s (2009) protocol in 10 sessions of 90 minutes, while the second experimental group received emotionally focused couple therapy based on Johnson’s (2012) model in 9 sessions of 90 minutes. The control group received no intervention. Data were analyzed using mixed repeated-measures analysis of variance in IBM SPSS Statistics version 18.Findings: The results of mixed repeated-measures analysis of variance demonstrated significant effects of group, treatment stages, and the interaction between group and treatment stages on self-oriented and other-oriented romantic relationship perfectionism (p < .001). Both cognitive-behavioral couple therapy and emotionally focused couple therapy significantly reduced romantic relationship perfectionism compared to the control group. The Bonferroni post-hoc test indicated significant differences between pretest and posttest scores as well as between pretest and follow-up scores (p < .001), while no significant differences were observed between posttest and follow-up stages, indicating the stability of treatment effects. Furthermore, Tukey post-hoc comparisons revealed that cognitive-behavioral couple therapy was significantly more effective than emotionally focused couple therapy in reducing both self-oriented and other-oriented perfectionism (p < .05).Conclusion: The findings suggest that both cognitive-behavioral couple therapy and emotionally focused couple therapy are effective interventions for reducing romantic relationship perfectionism among couples with marital conflict; however, cognitive-behavioral couple therapy demonstrated greater effectiveness. These results highlight the importance of targeting maladaptive cognitive patterns, unrealistic relational expectations, and emotional interactional processes in therapeutic interventions for distressed couples.